2014
DOI: 10.3389/fpls.2014.00526
|View full text |Cite
|
Sign up to set email alerts
|

Free sugar profile in cycads

Abstract: The sugars fructose, glucose, maltose, and sucrose were quantified in seven tissues of Zamia muricata Willd. to determine their distribution throughout various organs of a model cycad species, and in lateral structural roots of 18 cycad species to determine the variation in sugar concentration and composition among species representing every cycad genus. Taproot and lateral structural roots contained more sugars than leaf, stem, female strobilus, or coralloid roots. For example, taproot sugar concentration was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 81 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…40 mg·g −1 reported for Zamia muricata Willd. stems [ 22 ] was much less than that of C. micronesica stems. Although the same methods were used among these studies, the limited number of species do not enable an interpretation of these contrasting results for the two genera.…”
Section: Discussionmentioning
confidence: 99%
“…40 mg·g −1 reported for Zamia muricata Willd. stems [ 22 ] was much less than that of C. micronesica stems. Although the same methods were used among these studies, the limited number of species do not enable an interpretation of these contrasting results for the two genera.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that this may be a severe under estimation of Cycas megagametophyte starch content, as the starch content of C. micronesica megagametophyte was 65% at maturity. Marler and Lindstr€ om (2014) reported the sugar profile of an entire Zamia muricata Willd. megastrobilus was 65% fructose.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent report of fructose, glucose, and sucrose content in cycad tissues 3 sets the stage for designing continued research on how non-structural carbohydrates are involved in cycad pollination biology. Moreover, cycad horticulturists routinely harvest, store, and ship pollen prior to its use for successful pollination.…”
Section: Discussionmentioning
confidence: 99%
“… 2 As a result, we studied various aspects of free sugar content and reported that fructose, glucose, and sucrose were abundant in tissues from species representing every described cycad genera, and sugar content and stoichiometry varied greatly among organs. 3 The importance of these carbohydrates as forms of carbon storage, components of signaling, or regulators of cycad metabolism have not been determined to date.…”
mentioning
confidence: 99%